A Case Study of Albania’s Participation in PISA 2009 - Alfons Harizaj (Center for Educational Policy Studies Journal)
The paper presents a view of the results and progress of Albania in the Programme for International Students’ Assessments 2009 (PISA 2009). The overall goal and objectives of PISA are to offer support and expertise in the field of the evaluation of educational development factors in Albania. One of the methods successfully used for monitoring the achieved progress during the given study period was the estimation and comparison of results with the results of previous PISA participations. A broader comparison of these statistics with those of other PISA participants in the Albanian region provides a real picture of the situation, showing the progress Albania has made and indicating how effective Albania’s educational policies are.